Analysis of Character Values in The Folklore of The Origin Kretek Industry - Febrianti, Adhelia Putri; Velayali, Istifaiya; Resa Sirotun Hidayah, Eva; Mohammad Kanzunnudin (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This study aims to analyze the structure and character values contained in the folklore "Asal-Usul Industri Kretek". The research method used in this research is descriptive qualitative method. The method was chosen because the data in this study are in the form of words written descriptively and not in the form of numbers. The source of data in this study is a folklore book entitled "The Origin of the Kretek Industry" contained in the East Coast Folklore book written by Mohammad Kanzunnudin and published by CV Adhigama in 2024 which totals 230 pages. Data in the form of fragments of the story "The Origin of the Kretek Industry". Data collection techniques use listening and note-taking techniques. The data analysis technique used is the Milles & Huberman technique. The theory used in the structural analysis of folklore "Asal-Usul Industri Kretek" is Robert Stanton's Structuralism theory. Based on Robert Stanton's theory, the analyzed structure consists of story facts and literary means. In the structural part, the facts of the story contain theme, plot, character, and setting. The structure of literary means contains title, point of view, style and tone, symbolism, and irony. The theme in the story "Asal-Usul Indurtri kretek" is honesty and fortitude, the plot used is backward flow, and uses a third person point of view. The character values analyzed are the values contained in Permendikbud Number 20/2018 article 2 which contains five main character values, namely religious values, nationalism values, independent values, mutual cooperation values, and integrity values. These character values are shown from the sentences contained in the story. This research is expected to be able to become teaching material, especially to instill character values in students.